Pemakaian Komposisi Pada Pemberitaan Koran Malut Pos Edisi November 2020 - Idrus Ahmad (Peneliti.net, 2022)
This study aims to analyze and describe the use of composition in the November 2020 edition of the Malut Pos newspaper, including internal and external compositions. Using a qualitative descriptive method, this study also explores the forms of verbal compound words that are paired with nouns, adjectives, and adverbs. As well as how the process of combining words and words, words and subject matter, or subject matter and subject matter cannot be separated from each other. The source of data in this study is the November 2020 edition of the Malut Pos newspaper. the use of the composition is also a complete document.